Influence of voltage usymmetry on energy characteristics of crushers - Sinyavsky, O.; Savchenko, V.; Prudnikova, N.; Onischuk, M. (Energy and Automation, 2023)
As the conducted studies show, deviations of voltage asymmetry have the greatest impact on the electric drives of production machines and mechanisms. .Studies on the effect of voltage asymmetry on the technological characteristics of working machines and mechanisms have shown that their productivity decreases with voltage asymmetry. However, there are no studies on the influence of spring asymmetry on the energy characteristics of working machines.The purpose of the research is to determine the influence of voltage asymmetry on the energy characteristics of crushers.With voltage asymmetry, constant and variable losses in an asynchronous electric motor change.It is proposed to carry out an energy assessment of the electric drive of crushers based on the specific consumption of electricity.The influence of voltage asymmetry on the energy characteristics of crushers was studied. The dependence of the specific power consumption on the change in stiffness of the mechanical characteristics of the electric motor, which is caused by voltage asymmetry, is obtained. It was established that stiffness and power losses increase with voltage asymmetry. As a result, specific losses of electricity in the crushers electric drive increase.Key words: crusher, voltage asymmetry, power, crusher productivity, specific power consumption